All Days 2008
DOI: 10.2118/116306-ms
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Porosity and Permeability on the Membrane Efficiency of Shales

Abstract: This paper presents experimental data showing the dependence of shale membrane efficiency of water-base muds on its petrophysical properties and mud composition. Wellbore instability often occurs as a result of osmotic pressures that develop when shale is in contact with water-base muds. The osmotic pressures generated are proportional to the shale membrane efficiency. It is not currently possible to directly measure the shale membrane efficiency downhole. A pressure transmission technique was used to measure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 8 publications
(5 reference statements)
0
13
0
2
Order By: Relevance
“…This increase can also weaken the effect of drilling fluid invasion on the mechanical strength of the shale. On the other hand, increasing membrane efficiency can reduce the physical parameter values of the shale, such as porosity, permeability, and shale activity, according to Osuji (Osuji et al, 2008) and as shown in Figs. 11-13.…”
Section: Membrane Efficiency Affecting Water Entrancementioning
confidence: 99%
“…This increase can also weaken the effect of drilling fluid invasion on the mechanical strength of the shale. On the other hand, increasing membrane efficiency can reduce the physical parameter values of the shale, such as porosity, permeability, and shale activity, according to Osuji (Osuji et al, 2008) and as shown in Figs. 11-13.…”
Section: Membrane Efficiency Affecting Water Entrancementioning
confidence: 99%
“…Mechanical interactions are time independent phenomena and directly linked to the appropriate selection of mud weight (Zeynali, 2012). On the contrary, physico-chemical processes are time dependent (Lal, 1999;Osuji et al, 2008;Zeynali, 2012) and related to the interaction taking place between shales and Water Based Muds (WBMs). They induce swelling and reduces the strength of the wellbore, causing 'stuck pipe', bit balling, sloughing, reduction of the hole cleaning efficiency, and even loss of wells.…”
Section: Introductionmentioning
confidence: 99%
“…Zeynali, (2012) opines that mechanical interactions are time independent phenomena, which are directly linked to the appropriate selection of mud weight. On the contrary, physico-chemical processes are time dependent (Osuji et al, 2008;Zeynali, 2012) and related to the interaction between shales and water based muds (WBMs). It is therefore necessary, to address these cases with careful rock characterization and mud weight optimization.…”
Section: Introductionmentioning
confidence: 99%